2023
DOI: 10.1097/md.0000000000033751
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic modulation of gut microbiota by Bacillus coagulans MTCC 5856 in healthy subjects: A randomized, double-blind, placebo-control study

Abstract: Background: Probiotics are known to rebalance the gut microbiota in dysbiotic individuals, but their impact on the gut microbiome of healthy individuals is seldom studied. The current study is designed to assess the impact and safety of Bacillus coagulans (Weizmannia coagulans) microbial type culture collection 5856 (LactoSpore®) supplementation on microbiota composition in healthy Indian adults.Methods: The study participants (N = 30) received either LactoSpore (2 billion colony-forming units/capsule) or plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Twenty-five randomised controlled clinical trials [24,25, used single-strain Weizmannia coagulans probiotics. The most used strain (9 clinical trials) was GBI-30, 6086 [45,46,48,54,[56][57][58][59][60], followed by 5 clinical trials with the strain Unique IS-2 [25,41,47,51,53], 5 clinical trials with MTCC 5856 [24,38,39,44,55], and 2 clinical trials with LBSC (DSM 17654) [42,52]. The remaining four clinical trials were each conducted with a different strain, namely TBC169 [40], SNZ 1969 [43], BC30 [49], and T11 (IBRC-M10791) [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five randomised controlled clinical trials [24,25, used single-strain Weizmannia coagulans probiotics. The most used strain (9 clinical trials) was GBI-30, 6086 [45,46,48,54,[56][57][58][59][60], followed by 5 clinical trials with the strain Unique IS-2 [25,41,47,51,53], 5 clinical trials with MTCC 5856 [24,38,39,44,55], and 2 clinical trials with LBSC (DSM 17654) [42,52]. The remaining four clinical trials were each conducted with a different strain, namely TBC169 [40], SNZ 1969 [43], BC30 [49], and T11 (IBRC-M10791) [50].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining four clinical trials were each conducted with a different strain, namely TBC169 [40], SNZ 1969 [43], BC30 [49], and T11 (IBRC-M10791) [50]. The investigated beneficial effects of the probiotic strains included relieving symptoms of irritable bowel syndrome [42,46,51,53,55,58,59], constipation, diarrhoea, and other gastrointestinal symptoms [24,25,43,47,48,52,56,60], modulation of gut microbiota [38], function recovery treatment of non-fatty liver disease [45], after surgery [40] or in patients with rheumatoid arthritis [57], quality of life and glucose-and lipid-related biomarkers related to overweight or obese participants [44,49] or diabetic patients [50], absorption of protein or muscle integrity [41,54], and the skin anti-aging effect [39]. All clinical studies found at least one health benefit.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the strain produces organic acid (lactic acid) and short-chain fatty acids (SCFAs), which may lower the pH of the gut cavity, thereby inhibiting the growth of pathogens. These short-chain fatty acids play a pivotal role in the maintenance of overall gut health, intestinal morphology, and function ( 27 , 30 , 49 ). Moreover, W. coagulans MTCC 5856 is reported to have immunomodulatory properties in human colonic cells, which make the spores efficacious in the management of infectious diarrhea ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, oral administration of W. coagulans MTCC 5856 safely improved overall gut health in diarrhea predominant irritable bowel syndrome (IBS) patients (25). Recent studies have shown that it has therapeutic effects on intestinal diseases, such as acute diarrhea, antibiotic-related diarrhea, constipation, and colitis, via modulation of the microbiota composition, host immunity, and metabolism (25)(26)(27)(28)(29). Additionally, toxicological experiments and many clinical observations have shown that W. coagulans is safe and has no effect of mutagenicity, teratogenicity, or genotoxicity (28,30).…”
Section: Introductionmentioning
confidence: 99%
“…Пробіотичні організми підтримують корисні захисні бактерії, що містяться у системі травлення. Ці мікроорганізми необхідні для засвоєння поживних речовин і балансу кишкової флори [21].…”
unclassified